Perception and Experience of Online Learning During COVID-19 - Adeyinka Tella (The International Journal of Information, Diversity, & Inclusion)
This study examined the inclusivity of online education during the COVID-19 pandemic from the perspectives of LIS undergraduate students across four Nigerian universities. A quantitative method and survey design were employed, targeting undergraduate library and information science (LIS) students. A purposive selection of 20 students from years two, three, and four in the four universities resulted in a sample of 240 students. Data collection was conducted via a questionnaire distributed through Google Forms to students’ group forums, with the first 60 respondents from each university forming the sample. Of the 240 distributed questionnaires, 232 were returned and used for analysis. The findings revealed that online education during the pandemic was only partially inclusive: 70% of respondents indicated that many students could not participate in most online classes due to a lack of access to compatible technology, such as smartphones, tablets, and laptops. Platforms for online classes included Microsoft Teams, Google Classroom, Zoom, Moodle, and social media tools like blogs, Telegram, WhatsApp, and email. Course materials were sent via email and social media, but only 30% of students with access received them. The study concluded that online learning was not inclusive, as 70% of students were sidelined due to a lack of access to necessary devices and internet connectivity. For online learning to be inclusive, all students must be provided with compatible devices and data for connection to live classes. The government must also improve network infrastructure in rural areas to enable participation. This study is pioneering in focusing specifically on the inclusivity of online learning for LIS students during the pandemic.